Comparative analysis of Parkinson’s and inflammatory bowel disease gut microbiomes reveals shared butyrate-producing bacteria depletion - Maeve E. Krueger; Jake Sondag Boles; Zachary D. Simon; Stephan D. Alvarez; Nikolaus R. McFarland; Michael S. Okun; Ellen M. Zimmermann; Christopher E. Forsmark; Malú Gámez Tansey (npj Parkinson's Disease)
Abstract Epidemiological studies reveal that inflammatory bowel disease (IBD) is associated with an increased risk of Parkinson’s disease (PD). Gut dysbiosis has been documented in both PD and IBD, however it is currently unknown whether gut dysbiosis underlies the epidemiological association between both diseases. To identify shared and distinct features of the PD and IBD microbiome, we recruited 54 PD, 26 IBD, and 16 healthy control individuals and performed the first joint analysis of gut metagenomes. Larger, publicly available PD and IBD metagenomic datasets were also analyzed to validate and extend our findings. Depletions in short-chain fatty acid (SCFA)-producing bacteria, including Roseburia intestinalis, Faecalibacterium prausnitzii, Anaerostipes hadrus, and Eubacterium rectale, as well depletion in SCFA-synthesis pathways were detected across PD and IBD datasets, suggesting that depletion of these microbes in IBD may influence the risk for PD development.